BOOK REVIEW. THE LAST EMPIRE. THE FINAL DAYS OF THE SOVIET UNION - Crespo Alcázar, Alfredo (Journal of the Spanish Institute for Strategic Studies, 2018)
The subject of this book is highly topical because it refers to symbolism as well as togeopolitics. To this effect, the fact that stands out is that it was 25 years since the failedcoup to the then still Soviet Union in August of 2016 stands out. That failed couphad targeted toppling Gorbachev and, consequently, reversing the democratic changesthat he had brought to his country after becoming its maximum authority in 1985.Likewise, the dispute that Russia carries on with Ukraine today, in spite of Minsk II,has turned the former Soviet area into a protagonist of information and debate.